Reconstructing Legal Protection for Construction Service Providers in Construction Contracts Based on Pancasila Justice - Syamsiar Nurhayadi; Muhammad Ridwan Lubis; Dzaka Imtiyaz Iqbal; Andi Aina Ilmih; Naavi'u Emal Maaliki; Mahmoud Ali Al-Sobh (PT. Islamic Research Publiser, 2026)
Legal protection for construction service providers in construction contracts remains inadequate despite the enactment of Law Number 2 of 2017 on Construction Services. The existing regulatory framework imposes extensive obligations on service providers while failing to establish effective legal consequences for service users who delay contractual payments, thereby creating an imbalance of rights and obligations. This study aims to examine the regulatory weaknesses in the legal protection of construction service providers and to propose a reconstruction of the legal framework grounded in the principles of Pancasila justice. Employing a normative legal research method, the study analyzes statutory regulations, legal doctrines, judicial principles, and conceptual approaches to identify inconsistencies within the current legal regime. The findings reveal that the existing framework does not adequately ensure equitable contractual protection, as Article 47 lacks explicit provisions imposing sanctions on service users for late payments. These deficiencies are reflected in three interrelated dimensions: legal substance, which fails to provide balanced sanction mechanisms; legal structure, characterized by the absence of an independent and competent construction contract audit institution; and legal culture, where procurement practices continue to prioritize the lowest bid over fairness, professionalism, and service quality. To address these shortcomings, this study proposes a reconstruction of Article 47 by introducing mandatory payment obligations within agreed contractual periods, accompanied by enforceable sanctions in the form of material and immaterial compensation for unjustified payment delays. The proposed reconstruction integrates the values of Pancasila justice, emphasizing balance, proportionality, good faith, and social justice as fundamental principles of contractual relations. The study contributes to the development of construction contract law by offering a justice-oriented regulatory model that strengthens legal certainty, enhances contractual fairness, protects construction service providers, and promotes a more equitable legal system in Indonesia's construction services sector